Outdoor Recreation Areas: Capacity and the Formulation of Use Policy - Penz, Alton J. (Management Science, 1975)
The demand for outdoor recreation areas, such as national parks and forests, is growing. With this growth has come the realization that the administration of parks must maximize visitors' benefits from areas with limited visitor capacity. Visitor traffic has strained both man-made facilities as well as natural or ecological limits. Although individual locations within a park pose capacity restrictions, park capacity for visitors is a function also of visitor movement behavior among the locations. Solution of a linear programming model which represents visitor movement via transition matrices can help identify park capacity for visitors seeking various recreational experiences. The constraints of the model express capacities for both man-made facilities and ecological criteria as a function of visitor requirements. Program objectives derive from park policy about visitor use and benefits. Solutions to the program indicate appropriate long-range visitor admittance policy as well as provide insights for internal park control which is supportive of park objectives.